Mengembangkan Aspek Motorik Kasar Anak Menggunakan Problem Based Learning Melalui Permainan Tradisional Balogo - Jamiatun Adawiah; M.Dani Wahyudi (Jurnal Pendidikan Sosial Dan Konseling, 2025)
This study aims to develop gross motor skills of early childhood through the implementation of the Problem-Based Learning (PBL) model using the traditional game of balogo. The problem faced was the low coordination of gross motor movements among children at TK Putra II Banjarmasin, due to teacher-centered learning and lack of physical activity. The study used a qualitative approach with classroom action research (CAR) conducted in two cycles, each with two sessions. The subjects were 15 group B children. Research instruments included observation sheets for teacher activity, children’s activity, and gross motor skill development. Results showed improvements in teacher activity from 'sufficiently good' to 'very good', children’s activity from 'less active' to 'very active' (from 20% to 93%), and gross motor development from 'not yet developed' to 'very well developed' (from 7% to 93%). These findings indicate that the PBL model using the balogo game is effective in improving gross motor skills in early childhood.